Emerging roles of exosomes in the diagnosis and treatment of kidney diseases - Cao, Huanhuan; Li, Zixi; Ye, Jiajia; Lv, Yi; Zhang, Chun; Liang, Tao; Wang, Yumei (Frontiers in Pharmacology, 2025)
The complex etiology and spectrum of kidney diseases necessitate vigilant attention; the focus on early diagnosis and intervention in kidney diseases remains a critical issue in medical research. Recently, with the expanding studies on extracellular vesicles, exosomes have garnered increasing interest as a promising tool for the diagnosis and treatment of kidney diseases. Exosomes are nano-sized extracellular vesicles that transport a diverse array of bioactive substances, which can influence various pathological processes associated with kidney diseases and exhibit detrimental or beneficial effects. Within the kidney, exosomes derived from the glomeruli and renal tubules possess the ability to enter systemic circulation or urine. The biomarkers they carry can reflect alterations in the pathological state of the kidneys, thereby offering novel avenues for early diagnosis. Furthermore, research studies have confirmed that exosomes originating from multiple cell types exhibit therapeutic potential in treating kidney disease; notably, those derived from mesenchymal stem cells (MSCs) have shown significant treatment efficacy. This comprehensive review summarizes the contributions of exosomes from different cell types within the kidneys while exploring their physiological and pathological roles therein. Additionally, we emphasize recent advancements in exosome applications for the diagnosis and treatment of various forms of kidney diseases over the past decades. We not only introduce the urinary and blood biomarkers linked to kidney diseases found within exosomes but also explore their therapeutic effects. Finally, we discuss existing challenges and future directions concerning the clinical applications of exosomes for diagnostic and therapeutic purposes.